Grazing Problem and Control of the Rajasthan Desert - Mathauda, G. S. (Indian Forester, 1957)
The Rajasthan Desert, basically, is not a land of moving sand dunes. The tract is endowed with a reasonably rich flora, which is capable of forming a complete ground cover and thus immobilizing the sandy soils. Rainfall in this region being scanty and erratic, agriculture is a hazardous occupation. The thin human population subsists on the large number of goats, sheep, cows and camels they maintain. These cattle depend entirely on grazing and stall feeding is unknown. In years of normal or good rainfall there is a lush growth of grasses during the rainy season. This is gradually consumed by the cattle in the following months. A succession of low rainfall years, with resulting poor growth of grasses, leads to the destruction of this vegetation. Wind erosion is a logical consequence of this. Rationalization of grazing practices is essential for controlling the desert problem. This would involve reduction of the number of cattle to the safe bearing capacity of land, a proper distribution of grazing intensity and introduction of optimum schemes of rotational or seasonal grazing.